Luz y sombra en la obra de Bruno Violi (2009)
The present article is the result of a monographic study about the creative processes of the architect/painter Bruno Violi —a major representative of the Modern Movement in architecture who built most of his works in Colombia—, emphasizing on his treatment of light and shadow, bothon his graphic material and on his architectural projects.